The Paradox of the Frontal Lobe Paradox. A Scoping Review - Newstead, Simon; Lewis, Julia; Roderique-Davies, Gareth; Heirene, Robert M.; John, Bev (Frontiers in Psychiatry, 2022)
The ‘frontal lobe paradox’ highlights a phenomenon in which a subset of patients who possess frontal lobe damage and exhibit marked impairments in everyday life are still able to able to verbally describe a logical course of action relating to a task and perform well in interview and test settings. Such cases pose a challenge with regard to the assessment of mental capacity within clinical settings. Recent position articles state that the frontal lobe paradox is a well-known phenomenon within the field of neuropsychology, anecdotal reports from clinicians in the UK suggest this is not the case. Consequently, we conducted a scoping review to examine the breadth and depth of literature relating to the frontal lobe paradox. Searches were conducted using electronic databases and search engines, which were supplemented with a snowball search of the references used within relevant literature. We identified and reviewed 28 documents specifically related to the frontal lobe paradox. Nearly 50% of all identified academic texts published since 2000 were position articles that cited a handful of case studies published between 1936 -1986 as evidence for the phenomenon. We also observed instances of articles citing position articles as evidence of the frontal lobe paradox. Overall, our findings indicate a lack of readily accessible research specific to the frontal lobe paradox. In particular, there is a lack of contemporary research specific to the subject and an absence of clarification as to which syndromes and disorders are included within the term.